2009
DOI: 10.1111/j.1468-3083.2009.03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the laboratory diagnosis of Chlamydia trachomatis infections in East European countries

Abstract: The present guidelines aim to provide comprehensive information regarding the laboratory diagnosis of infections caused by Chlamydia trachomatis in East European countries. These recommendations contain important information for laboratory staff working with sexually transmitted infections (STIs) and/or STI-related issues. Individual East European countries may be required to make minor national adjustments to these guidelines as a result of lack of accessibility to some reagents or equipment, or laws in a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…The high cost of these tests didn’t allow the conduct of a populational study, but the studied lot can also provide us with the conclusion that in the selected population of north‐eastern Romania, using the major selection criterion – age, as well criteria based on risk‐factors present in the C. trachomatis infection, with international recognized detection tests, trained lab personnel, harvesting, depositing and transport according to the international norm guides, 7 accurate sampling conditions regarding the patient’s treatment status, the sampling moment, we did not obtained a high frequency of the C. trachomatis infection which justifies including this determination into a screening, according to the literary recommendations.…”
Section: Chlamydia Trachomatis Incidence and Association With Bactermentioning
confidence: 99%
“…The high cost of these tests didn’t allow the conduct of a populational study, but the studied lot can also provide us with the conclusion that in the selected population of north‐eastern Romania, using the major selection criterion – age, as well criteria based on risk‐factors present in the C. trachomatis infection, with international recognized detection tests, trained lab personnel, harvesting, depositing and transport according to the international norm guides, 7 accurate sampling conditions regarding the patient’s treatment status, the sampling moment, we did not obtained a high frequency of the C. trachomatis infection which justifies including this determination into a screening, according to the literary recommendations.…”
Section: Chlamydia Trachomatis Incidence and Association With Bactermentioning
confidence: 99%
“…It is recognised that national adjustments to these guidelines may be needed in some eastern European countries to meet local laws and health strategies and according to the availability of kits and reagents. They are a consensus document of the Eastern European Sexual and Reproductive Health (EE SRH) Network [11,12] and comprise one element of a series of guidelines aimed at optimising, standardising and providing guidance on quality assurance of laboratory testing for reproductive tract infections [13][14][15][16]. They are primarily intended for professionals testing specimens from patients at sexual healthcare clinics but may also be helpful for community-based screening programmes.…”
Section: Importance Of Laboratory Diagnosis Of Genital Herpesmentioning
confidence: 99%
“…Through many surveys of diagnostic strategies, laboratory diagnostic methods, case reporting and epidemiological surveillance among the network countries, the EE SRH has shown that surveillance systems are incomplete, and that many of the individual diagnostic tests and approaches used are suboptimal and do not provide a definitive diagnosis for several STIs (i.e. in accordance with recommended international guidelines) 4–7 . For instance, serological tests are used to diagnose C. trachomatis infection in up to 70% of clinical laboratories in several EE countries, whereas routine screening for gonococcal infections in women is largely conducted by the sole use of microscopy of Gram‐stained cervical smears 8…”
Section: Introductionmentioning
confidence: 99%
“…in accordance with recommended international guidelines). [4][5][6][7] For instance, serological tests are used to diagnose C. trachomatis infection in up to 70% of clinical laboratories in several EE countries, whereas routine screening for gonococcal infections in women is largely conducted by the sole use of microscopy of Gram-stained cervical smears. 8 In this context, the NSCP conference was organized to join together experts from different Western, Central and Eastern European countries to share knowledge and expertise.…”
Section: Introductionmentioning
confidence: 99%